295 PREDICTION OF MORBIDITY AND MORTALITY AFTER THORACOABDOMINAL ESOPHAGEAL SURGERY. (17th September 2021) - Nilsson, Erik; Olsén, Monika Fagervik; Trölle, Ulrika; Eriksson, Frances; Hermansson, Michael
Abstract: : Complications after esophageal cancer surgery has been shown to decrease long-term quality-of-life and to increase the risk of postoperative mortality, making patient selection important. The physical strength of the individual patient is likely to affect the patient's chance of withstanding a major surgical intervention. The aim of this study was to evaluate if validated physical tests can predict the risk of postoperative complications after a thoraco-abdominal esophagectomy. Methods: All patients who had a thoraco-abdominal esophagectomy at three Swedish university hospitals from 2014–2017 were eligible for inclusion in this prospective study. In addition to a bicycle test, patients were evaluated preoperatively by a physiotherapist using eight validated physical tests. Data on postoperative complications were extracted from the Swedish National Registry for Esophageal and Gastric Cancer. Patients were divided into two groups according to Clavien Dindo (CD) classification of the most severe complication (CD 1–2 and CD 3–5). Tests results were compared between the groups. We also compared performance in each validated test to the risk of specific complications. Results: A total of 114 patients were enrolled. 26 patients were excluded because of missing data leaving 88 patients for statistical analyses. Total 90-days mortality was 2.3%. Patients who suffered from an anastomotic leak after surgery had a significantly lower performance in the bicycle test. Performance in the preoperative shoulder abduction- and 6-minute-walk tests were significantly lower in patients who suffered from pneumonia or cardiovascular complications. Patients scoring in the lowest quartile in the hand grip-strength test had a higher frequency of complications rated as CD 3–5. No other significant differences could be shown between the CD groups. Conclusion: In this prospective multicentre study, we found a connection between patient performance on four different preoperative physical tests (bicycle test, shoulder abduction test, 6-minute walk test and hand grip-strength test) and the risk of postoperative complications. We believe that these relatively simple tests can help the surgeon when evaluating the surgical risk for the individual patient.